SPE Annual Technical Conference and Exhibition 2008
DOI: 10.2118/116173-ms
|View full text |Cite
|
Sign up to set email alerts
|

Testing of New PDC Cutter Edge Geometry Doubles Penetration Rate and Reduces Torque

Abstract: A new edge preparation of Polycrystalline Diamond Compact (PDC) cutters has been developed to target applications where either weight or torque is limited. This paper describes the geometry, which differs considerably from existing thermostable product.Initial testing at atmospheric conditions in a drilling laboratory shows a 30% reduction in torque and a 100% increase in penetration rate when compared to conventional cutter geometry. Secondary testing was conducted with drill bit designs at a non-commercial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…3. The effect of altered chamfer edge geometry was presented by Barton et al (2008) providing increased ROP, while also seeing a reduction in torque as the rock is drilled more efficiently. It was confirmed that stability of the PDC bit design was not affected by this change in terms of the cutter aggressiveness, hence it was thought to be a better way of introducing a more aggressive and efficient PDC cutting structure to the hard chalk application.…”
Section: A Different Approach To Bit Selectionmentioning
confidence: 99%
“…3. The effect of altered chamfer edge geometry was presented by Barton et al (2008) providing increased ROP, while also seeing a reduction in torque as the rock is drilled more efficiently. It was confirmed that stability of the PDC bit design was not affected by this change in terms of the cutter aggressiveness, hence it was thought to be a better way of introducing a more aggressive and efficient PDC cutting structure to the hard chalk application.…”
Section: A Different Approach To Bit Selectionmentioning
confidence: 99%
“…While drilling the Lance Pool it is common to penetrate over 30 hard sandstone units. The sand-shale sequences found in the upper, middle, and lower Lance have unconfined compressive strengths ranging between 10 and 20 ksi, with confined compressive strengths averaging between 20 and 30 ksi, and as high as 100 ksi (Barton et al 2008) (Gent et al 2009). Much of the bit dysfunction observed is associated with the transition between softer and harder strata.…”
Section: Introductionmentioning
confidence: 99%